An Ethereum-based point of sale system for retail stores - Maria Betânia Benita Afonso (2021)
The use of cryptocurrencies and their use on retail has evolved a lot throughout these last few years. Thus, the tendency for a progressive increase in the demand for methods of using these currencies is to be expected and is predicted to be the future. Thus, the main objective of this dissertation is to study and implement a strategy capable of making payments in Point of Sale (POS) systems using ethereum in order to keep up with the demand of the public.